An operating model for the accounting information system implementation - Hietala, Jukka (My University, 2020)
Accounting information systems produce vital data to organizations and work as a core part of organizations’ decision making. Furthermore, digitalized accounting has increased efficiency of corporations by 30%. Many organizations want to transfer to digitalized accounting to gain benefits of digitalization. Implementation of an information system, however, is a difficult process and only 40% of them fulfill set expectations. The goal of this research was to create a meta artifact which is a group of guidelines. The artifact is designed to work as a general guidance on how to implement an accounting information system in a company. Design science research is chosen as the research method because the goal of the artifact was to be as practical as possible in the target environment. The theoretical framework consists of accounting information systems and their implementation. Data gathering methods for the research were group interviews and observations which were conducted to gain a better understanding of the implementation processes. Group interviews and observations were conducted in case company Alpha which has successfully completed an accounting information system implementation. Usability of the artifact was important for the research because beneficial artifact must be highly usable and applicable in different accounting information system implementations. Usability of the artifact was tested in the environment of Alpha by conducting a retrospective simulation. The artifact was then evaluated how it performed on the target environment. The result of the research gives answers to two questions: how to implement an accounting information system and what should be considered when transferring from a modern AIS to another modern AIS.
Keywords: fi=Tietojärjestelmätiede|en=Information Systems|; fi=Teknisen viestinnän maisteriohjelma|en=Master's Programme in Technical Communication|sv=Magisterprogrammet i teknisk kommunikation|